Development of Locomotor Skills in Children Aged 4-5 Years - Nur Lu’luul Hasanah; Fitri Ayu Fatmawati; Mushab Al Umairi (EDUTEC : Journal of Education And Technology, 2024)
This study focuses on understanding the aspects of locomotor skill development in children aged 4-5 years at TK Dharma Wanita Persatuan Bengkololor Benjeng. The objective is to identify the causes of locomotor issues in "Ananda M" and to emphasize the crucial role of teachers and parents in encouraging and cultivating habits that support locomotor development while boosting the child’s self-confidence in physical activities. The study employs a qualitative approach using a case study method. The findings indicate that "Ananda M" demonstrates slight delays in locomotor development compared to peers. This is evident in activities such as running games, where the child appears unsteady; in arched ladder games, where the child trembles or hesitates due to a fear of heights; and in two-foot jumping games, where the child lacks self-confidence, opting to step rather than jump. These issues are attributed to several factors, including a lack of stimulating environmental conditions in the living area, limited social interaction, and traumatic experiences.